Rate of coastal erosion along Tanjung Piai - Tai, Lai Wai; Seow, Ta Wee (2004)
Tanjung Piai or Piai headland, located in the south of Malaysia, is suffering from an excessive coastal erosion due to wave attack and oil spills. It seems that human activities have triggered the erosion at an alarming rate. Mangrove forest fringing the coast of Tanjung Piai which is the habitat of many threatened and vulnerable species is also destroyed bit by bit. It has been found that the rate of erosion is increased after the opening of an adjacent port in 1999. Higher energy waves generated by ships navigating through Tanjung Piai waters have been the cause of the erosion. Before year 1997, the erosion rate was found to be 0.25 m/year. However, this study has shown that the rate of erosion has been increased tremendously; which is up to 3.00 m/year from coastline photographs taken in 2003.